2010
DOI: 10.3851/imp1507
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Antagonists: Host-Targeted Antiviral Agents for the Treatment of HIV Infection, 4 Years on

Abstract: . We reviewed the various categories of agents and compared the three small-molecule CCR5 antagonists that had progressed to clinical development: maraviroc, vicriviroc and aplaviroc. At that time, several key questions needed to be addressed by large-scale clinical trials, concerning not only the clinical efficacy and long-term safety of these agents, but also the pathways to CCR5 antagonist resistance in vivo and the effect of therapeutic administration of CCR5 antagonists on CXCR4-using virus populations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 79 publications
2
34
0
Order By: Relevance
“…The efficacy, tolerability and toxicity profiles of PRO 140 have been assessed by several preclinical and clinical studies, which showed promising results (reviewed in [75]). Of note is the evidence of activity shown by PRO 140 against escape mutants with cross-class resistance to small molecule CCR5 inhibitors [76]; however, as a complex biological molecule requiring parenteral administration, PRO 140 faces a different set of development challenges compared to the orally bioavailable small molecule compounds [77]. Human CCR5mAb004 antibody also performed well in early clinical trials [22].…”
Section: Anti-ccr5 Antibodiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The efficacy, tolerability and toxicity profiles of PRO 140 have been assessed by several preclinical and clinical studies, which showed promising results (reviewed in [75]). Of note is the evidence of activity shown by PRO 140 against escape mutants with cross-class resistance to small molecule CCR5 inhibitors [76]; however, as a complex biological molecule requiring parenteral administration, PRO 140 faces a different set of development challenges compared to the orally bioavailable small molecule compounds [77]. Human CCR5mAb004 antibody also performed well in early clinical trials [22].…”
Section: Anti-ccr5 Antibodiesmentioning
confidence: 99%
“…The limited information currently available from published results of clinical studies suggests that the escape process from small molecule CCR5 inhibitors in vivo bears similarities to that observed in vitro; clinical resistance is also likely to map to the V3 region of gp120, but the lack of consistency of observed mutations renders impossible the prediction of in vivo resistance by sequence analysis at present (reviewed in [72,77,117,141]). As mentioned above, two pathways of virological escape from the selection pressure of CCR5 antagonists have been identified: continued use of CCR5 via selection of R5 virus that can use drug-bound CCR5 for entry in addition to free coreceptor and expansion of pre-existing minority populations of dual-tropic or X4 virus (collectively called "CXCR4-using" viruses).…”
Section: In Vivo Resistance: Potential Expansion Of Pre-existing CXCmentioning
confidence: 99%
See 3 more Smart Citations